DPP-4 Inhibition and the Path to Clinical Proof - Ahrén, Bo (Frontiers in Endocrinology, 2019)
In the 1990s it was discovered that the enzyme dipeptidyl peptidase-4 (DPP-4) inactivates the incretin hormones glucagon-like peptide-1 (GLP-1) and glucose-dependent inulinotropic polypeptide (GIP). This formed the basis for DPP-4 inhibition as a glucose-lowering therapy since DPP-4 inhibition results in remained elevation of levels of the two incretin hormones which lowers circulating glucose through stimulating insulin secretion and inhibiting glucagon secretion. Since then, several small orally available molecules have been developed with DPP-4 inhibitory action. Early studies in the 1990s showed that the DPP-4 inhibitors improve glycemia in animals and subsequent clinical studies during the 2000s showed glucose-lowering action also in human subjects with type 2 diabetes. This was seen when DPP-4 inhibitors were used both as monotherapy and as add-on to metformin, to sulfonylureas, to tiazolidinediones and to exogenous insulin. The DPP-4 inhibitors were also found to have a low risk of adverse events, including hypoglycemia. Five of the DPP-4 inhibitors (sitagliptin, vildagliptin, alogliptin, saxagliptin and linagliptin) were approved by different regulatory authorities and entered the marked between 2006-2013. DPP-4 inhibitors have also undergone long-term cardiovascular outcome trials, showing non-inferiority for risk of major acute cardiovascular endpoints. Also the risk of other potential adverse events is low in these long-term studies. DPP-4 inhibitors are at present included in guidelines as a glucose-lowering concept both as monotherapy and in combination therapies. This article summarizes the development of the DPP-4 inhibition concept from its early stages in the 1990s. The article underscores that the development has its basis in scientific studies on pathophysiology of type 2 diabetes and the importance of targeting the islet dysfunction, that the development has been made possible through academic science in collaboration with the research-oriented pharmaceutical industry, and that the development of a novel concept takes time and requires focused efforts, persistence and long-term perserverance.